Chemiluminescence Immunoassay: Basic Mechanism and Applications - Azim, Mohammad Anwar ul; Hasan, Mizanul; Ansari, Israque Hossain; Nasreen, Faria (Bangladesh Journal of Nuclear Medicine, 2018)
Chemiluminescence immunoassay (CLIA) has been widely applied in different fields including environmental monitoring, liquid chromatography, clinical diagnosis; food safety, pharmaceutical analysis, immuno- and gene probe assays, as a promising approach for selective, sensitive, rapid and simple analysis. It is often necessary to detect a large number of complicated or low-abundance samples. However, traditional methods need great consumption of time, reagents and labor, which limit their clinical applications. As a result, rapid, high-throughput, sensitive and low-cost detection methods have become the development trend of CLIA. A new chemiluminescence immunoassay analyzer with advanced acridinium ester (AE) technology will be installed at the radioimmunoassy laboratory of National Institute of Nuclear Medicine and Allied Sciences (NINMAS) shortly. In conjunction with the existing Radioimmunoassay (RIA), Immunoradiometric assay (IRMA) and DissociationEnhanced Lanthanide Fluorescent Immunoassay (DELFIA), introduction of chemiluminescence immunoassay (CLIA) technology will expand the activities of in vitro immunoassay. It will also improve the research and development activities of in vitro division of NINMAS. In this review article, we have summarized the basic principle of chemiluminescence immunoassay and its applications. A comparison of RIA, CLIA and enzyme-linked immunosorbent assay (ELISA) was also briefly described in the article. Bangladesh J. Nuclear Med. 18(2): 171-178, July 2015